Design thinking as an approach for sustainability - Jelena, Djokikj; Sofija, Sidorenko (The Design Society, 2022)
There are not lot of evidence of implementation of the design thinking approach into the academia, this is why we wanted to conduct this kind of research. We worked with students on design with social impact and implemented the design thinking approach as a problem-solving approach. Our finding were that this approach fits perfectly for this kind of problems and is also suitable for most academia curriculums.
Keywords: Design thinking, conceptual design, sustainability, design with social impact